Sources of contaminated flood sediments in a rural–urban catchment: Johnson Creek, Oregon. Issue 4 (30th October 2018) - Chang, Heejun; Allen, Deonie; Morse, Jennifer; Mainali, Janardan
Abstract : This study investigated the delivery of contaminated sediments to the channel network by urban drainage systems in Johnson Creek in Oregon, USA. Concentrations of five heavy metal concentrations measured in 136 samples collected from 37 stormwater outfalls and 99 bed sampling points were analysed. While concentrations of zinc, cadmium, and lead increased with distance downstream in Johnson Creek, this was not the case for chromium and copper. Zinc, copper, and cadmium concentrations in outfalls were significantly higher than those in the stream bed, indicating that stormwater runoff is responsible for delivering contaminated sediments to Johnson Creek. Zinc concentrations in outfalls were negatively associated with elevation and slope in the contributing subcatchment, and positively with impervious cover. However, no statistically significant relationships were found between the other heavy metal concentrations and subcatchment variables. These findings demonstrate that relationships between sediment‐related, heavy metal concentrations, and subcatchment characteristics in this heterogeneous, rural–urban catchment are more complex than those found in situations where land‐use is more segregated, questioning the applicability of commonly held assumptions regarding changes in the sources and delivery paths of flood‐related, sediment‐associated pollutants that accompany urbanisation.